PERANCANGAN DAN PENGEMBANGAN PERANGKAT LUNAK PERENCANAAN KEBUTUHAN MATERIAL - Antono Adhi; Enty Nur Hayati; Agus Setiawan (Jurnal Ilmiah Dinamika Teknik, 2011)
Computerized ordering and scheduling system for manufacturing and fabrication industries, it uses bill of materials data, inventory data, and master production schedule to project what material is required, when, and in what quantity. MRP phases orders for dependent-demand items (such as raw materials, components, parts) over a period to synchronize flow of materials and in in-process inventories with production schedules. It also computes and tracks effect of hundreds of variables such as new orders, changes in various capacities, overloaded production centers, shortages, and delays by suppliers, and feeds financial data into the accounting system. In contrast to just in time inventory (a demand-pull production system), MRP is a plan-push system, and in contrast to advanced planning system (a forward scheduling system) it is a backward-scheduling system. Keywords: Material Requirement Planning, Production Schedules, Inventor